Operationalizing the soil health metaphor to create sustainable food systems, with a focus on smallholder farming in the Global South - Pulleman, Mirjam Margreet (2023)
- Restoring / enhancing soil health is key for sustainable intensification and regenerative agriculture in the Global South, while reducing vulnerability of smallholder farmers to climate change. - A flexible framework is proposed that can be used to target, monitor and adapt soil health interventions with relevant stakeholders - Development of biological soil health indicators and assessment methods require more research – given the key role of soil biology for soil health/functions - High fertilizer costs, attention for soil health have led to the promotion of “smallholder-friendly” “biofertilizers” especially in Latin America, but scientific evidence and mechanistic understanding is lacking. - Robust, hypothesis based, experimental research is needed to develop targeted, proven methods, alongside feasibility studies and development of business models